Gender and Technology. - Sweetman, Caroline (Oxfam focus on gender, 1999)
The delivery of new technologies to communities in developing countries has been hailed as the key to economic and social progress. However, women's experiences show that this view is an exaggeration, over-simplifying the potential of technology to deliver `development`. Different technologies in varying social contexts offer opportunities to challenge existing barriers to economic and political participation, but they can also be used to consolidate existing imbalances of power. This collection of articles from Gender and Development considers technologies of many kinds, including those intended to save women`s labour, to enable them to control their fertility and to learn and communicate using computer technology. Writers include Radhika Gajjala and Annapurna Mamidipudi, Heather Schreiner and Maggie Foster.